2020
DOI: 10.1002/path.5436
|View full text |Cite
|
Sign up to set email alerts
|

Cisd2: a promising new target in Alzheimer's disease

Abstract: The CISD2 gene encodes the CDGSH iron‐sulfur domain‐containing protein 2. Cisd2 is involved in mammalian lifespan control, the unfolded protein response, Ca2+ buffering, and autophagy regulation. It has been demonstrated previously that Cisd2 deficiency causes an accelerated ageing phenotype characterised by the accumulation of damaged mitochondria, while Cisd2 overexpression leads to mitochondrial protection against typical age‐associated alterations. Accumulating data suggest that neuronal amyloid‐beta (Aβ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…A recent analysis shows that iron levels and related redox activities in the cortex and cerebellum were increased in patients in the preclinical stage of AD [ 89 ]. As the Cisd2 gene encodes the CDGSH iron–sulfur-domain-containing protein 2, Cisd2 overexpression attenuates AD pathogenesis by guaranteeing mitochondrial quality and synaptic functions [ 91 ]. Therefore, brain iron accumulation has become a major pathological feature of the early onset of AD.…”
Section: Iron Metabolism and Neurodegenerative Diseasesmentioning
confidence: 99%
“…A recent analysis shows that iron levels and related redox activities in the cortex and cerebellum were increased in patients in the preclinical stage of AD [ 89 ]. As the Cisd2 gene encodes the CDGSH iron–sulfur-domain-containing protein 2, Cisd2 overexpression attenuates AD pathogenesis by guaranteeing mitochondrial quality and synaptic functions [ 91 ]. Therefore, brain iron accumulation has become a major pathological feature of the early onset of AD.…”
Section: Iron Metabolism and Neurodegenerative Diseasesmentioning
confidence: 99%
“…High CISD2 expression was significantly correlated with poor prognosis in different tumors. In gastric cancer, CISD2 is significantly upregulated and is markedly associated with clinical stage, venous invasion, TNM classification, and lymphatic invasion [ 46 ]. Yang et al [ 40 ] found that CISD2 expression was abnormally upregulated in human laryngeal squamous cell carcinoma tissues and was remarkably correlated with T stage, lymphatic invasion, clinical stage, and progress of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…CISD2 KO mice not only recapture these phenotypes but also present nerve and muscle degeneration in association with mitochondrial damage, and autophagy-mediated cell death (Chen et al. 2009a; 2009b; Nobili et al., 2020). In addition, the lysosome is used in the cellular uptake of iron, and the lysosome and other structures associated with autophagy (e.g., autophagosome) are essential for the recycling of iron (Kurz et al., 2011).…”
Section: Discussionmentioning
confidence: 99%